Visualising the IIUM's Philosophy, Vision, Mission, Islamisation Policy and Sejahtera Objectives - Hassan, Nur Jannah (Centre for Islamisation (CENTRIS), 2021)
Visualising is a collection of information, posters and infographics that have been designed to assist the community of the International Islamic University Malaysia—staff, alumni and students—in understanding her ideals and fundamental concepts, and further internalising and translating them into self-improvement, teaching and learning, administration practices, research and consultancies, projects, community outreach and engagements, etc. In short, in establishing the whole ecosystem towards realizing the University’s raison d’etre. This work is an effort to help preserve the IIUM community’s firm grounding on the University’s noble and sacred Philosophy, Vision and Mission as her living legacy, in “leading the way” to a better future of the world. This book shall be read with its predecessor, the IIUM Policies and Guidelines on Islamisation, CENTRIS, IIUM: 2013, as well as with the newly published Sejahtera Academic Framework: Humanising Education for Raḥmatan li’l-‘Ālamῑn Post-COVID-19 Disruptions, KCA, IIUM: (2021).